(untitled) (Islamic Sciences Journal, 2023)
ABSTRACT Having concluded this modest research, I concluded that: The system of marriage under the law of Islam is a system that preserves both women and men. The system of marriage in Islam has given both husband and wife their rights without attacking each other on their rights. The issue of polygamy is a necessity necessitated by the law of Islam. The organization of Islam for polygamy is a pride of Islam. Polygamy exists before the law of Islam, but Islam regulated that legislation. Islam has adopted a system of polygamy but did not leave it without regulation but make conditions and controls for this system. The system of polygamy is a solution to problems that may occur by the family, which may lead to the collapse of the family and the solution is only polygamy such as wife disease or sterility. Islam has solved the problems of marriage through the legislation of polygamy while Western systems remained confused in solving those problems, such as increasing the number of women over the number of men as it usually occurs after the wars.